2017
DOI: 10.1021/acs.iecr.7b01416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetic Model for Autocatalysis in Liquid–Liquid System: Oxidation of Dibutyl Sulfide with Aqueous Hydrogen Peroxide

Abstract: The oxidation of dibutyl sulfide with aqueous hydrogen peroxide as a liquid−liquid reaction was investigated. The autocatalysis, solubility of H 2 O 2 in organic phase, and effects of temperature, stirring speed, initial organic DBSO concentration, and initial aqueous H 2 O 2 concentration were studied. Solvent effect of dibutyl sulfoxide was proposed for liquid−liquid autocatalysis. The intrinsic reaction was considered as the determining step, and all the other steps were considered as equilibrium processes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This result suggests that compound 1 could be oxidized into DMSO by H 2 O 2 in the juice model solution. Previous reports demonstrated that some volatile sulfur compounds could be selectively oxidized to sulfoxides and disulfide by H 2 O 2 . As shown in Figure , the DMSO content tended to be stable because of the heavy consumption of reactants ( 1 or H 2 O 2 ) after 16 min, and it exceeded about 10.5 mg/L after the reaction for 120 min, when the amount of H 2 O 2 that had been added was 10 μL/100 mL 1 glucose solution (about 10 mmol/L). These results indicate that compound 1 reacted readily with H 2 O 2 and that about 93% of compound 1 in the model solution (9.0 mg/L) oxidized into DMSO in the end.…”
Section: Results and Discussionmentioning
confidence: 86%
“…This result suggests that compound 1 could be oxidized into DMSO by H 2 O 2 in the juice model solution. Previous reports demonstrated that some volatile sulfur compounds could be selectively oxidized to sulfoxides and disulfide by H 2 O 2 . As shown in Figure , the DMSO content tended to be stable because of the heavy consumption of reactants ( 1 or H 2 O 2 ) after 16 min, and it exceeded about 10.5 mg/L after the reaction for 120 min, when the amount of H 2 O 2 that had been added was 10 μL/100 mL 1 glucose solution (about 10 mmol/L). These results indicate that compound 1 reacted readily with H 2 O 2 and that about 93% of compound 1 in the model solution (9.0 mg/L) oxidized into DMSO in the end.…”
Section: Results and Discussionmentioning
confidence: 86%
“…The oxidation of organic thioethers with H 2 O 2 is notably slow and depends on the concentration of both reactants. 26,57 Thus, we chose to use a large excess of…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of organic thioethers with H 2 O 2 is notably slow and depends on the concentration of both reactants. 26,57 Thus, we chose to use a large excess of H 2 O 2 (90 equivalents for PM16 and 46 for PM32) compared to the thioether units of the polymers to obtain an overview of the response times and behavior of these micelles. PM16 (6.7 mM thioether units at 6.8 mg mL −1 ) and PM32 micelles (13 mM thioether units at 6.8 mg mL −1 ) in PB/D 2 O 9 : 1 were combined with 2.0 wt% H 2 O 2 (600 mM) at 37 °C and studied by 1 H NMR spectroscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation of organic thioethers with H2O2 is notably slow and depends on the concentration of both reactants. [24,50] Thus, we chose to use a large excess of H2O2 (90 equivalents for PM16 and 46 for PM32) compared to the thioether units of the polymers to obtain an overview of the response times and behavior of these micelles. PM16 (6.7 mM thioether units at 6.8 mg/mL) and PM32 micelles ( 13mM thioether units at 6.8 mg/mL) in PB/D2O 9:1 were combined with 2.0 wt% H2O2 (600 mM) at 37 °C and studied by 1 H NMR spectroscopy (Figure 2C and Figure S8 for PM16 and PM32, respectively).…”
Section: H2o2 Induced Oxidation and Hydrolysis Of P(dman-b-mtpam) Micellesmentioning
confidence: 99%